Barriers and Challenges To the Implementationof Green Building Development Ingresik - Dinar Melayani; Tri Joko Wahyu Adi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Sustainable development has become a key focus in addressing the challengesof climate change and environmental degradation. One crucial solution in achievingsustainable development is the implementation of green buildings. This study aimstoidentify and analyze the barriers and challenges encountered in the implementationof green buildings in both government and private projects. The findings of this researchare expected to be useful for local governments in formulating effective strategiestoincrease the number of green buildings in the city. In this research, the variablesof barriers and challenges are obtained through a literature review of international anddomestic journals that examine the obstacles and challenges in the implementationof green buildings. The study will employ several methods, including the RelativeImportance Index (RII), to identify the most influential barriers and challenges totheimplementation of green buildings. The respondents in this study are stakeholdersinvolved in the development of Gresik City, including government officials, consultants, and contractors. The results of this study are expected to identify the main barriersandchallenges in the implementation of green buildings in Gresik City. The results of thisresearch show that the 3 largest ranking barriers variables are the practice of illegal levies in obtaining permits, the limited number of BGH consultants, the opportunitytobe invited to government tenders needs to be increased. Meanwhile, the 3 largest ranking challenge variables are limited research on environmentally friendly buildingwork methods, lack of investment in environmentally friendly materials, limitededucational infrastructure for trained teachers.